Enhancing spoken production on B1 Teenagers at Pucesa through Task-Based communicative activities - Guerra Mera, Fanny del Carmen (2014)
Task-based Approach is a significant component in the development of language teaching curriculum. This approach uses tasks, which are goal-oriented and learner-centered that help students use real language to get a specific outcome that in the case of this study is to communicate in a comprehensible manner. Speaking is an essential part of second language learning and teaching. Teaching speaking is not just to let students to repeat or memorize dialogues, but they should be able to use the language in real life situations. This dissertation seeks to demonstrate that the use of Task-based Learning Approach and its framework enhance spoken production in B1 students when they do different speaking activities that give them opportunities to use the target language meaningfully. The activities adapted to TBL framework encourage students to interact and participate in real life situations using appropriate attention-getting devices and conversation strategies. This study will be an interesting source for teacher to create dynamic and novel speaking lessons for their students in order to promote interaction and real communication